The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.9790/0837-19858795
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behaviour and Demographic Factors among Oil Workers in Nigeria

Abstract: Even though numerous epidemiology studies have examined the patterns of mortality in refineryworkers and petroleum distribution workers and even on production and pipeline workers whose primary exposure was to crude oil (Divine and Hartman, 2000)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
(20 reference statements)
0
7
2
1
Order By: Relevance
“…These results are consistent with those produced by Farzianpour et al [8] relating to gender factor, and Altuntas & Baykal [9] regarding the impact of employees' age. However, the result appeared contrary to those of Francis [10] who reported that employees' gender had no impact on OCB. Similarly, El-Badawy et al [13] found no significant relationship between gender, age, years of experience and education level, and OCB among Egyptian and Mexican employees.…”
Section: Resultscontrasting
confidence: 97%
See 2 more Smart Citations
“…These results are consistent with those produced by Farzianpour et al [8] relating to gender factor, and Altuntas & Baykal [9] regarding the impact of employees' age. However, the result appeared contrary to those of Francis [10] who reported that employees' gender had no impact on OCB. Similarly, El-Badawy et al [13] found no significant relationship between gender, age, years of experience and education level, and OCB among Egyptian and Mexican employees.…”
Section: Resultscontrasting
confidence: 97%
“…Significant relations have been found between gender of managers, and their education level with OCB [8]; and between some employees' demographics such as age, work position, and institutional experience in addition to professional characteristics and OCB [9]. However, Francis [10] reported that employees' gender, educational level, and marital status had not affected their practicing of OCB. Beyond the employees' demographics, working environment had also influenced OCB; and psychological empowerment had a positive impact on OCB [11].…”
Section: Organizational Citizenship Behavior and Employees' Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As about the education level of workers (Table 1) (Francis 2014). This difference in the education distribution could be explained by being a multinational company in Nigeria compared to policy of employing Yemeni people with lower educational levels particularly with the current conflict situation in Yemen.…”
Section: Discussionmentioning
confidence: 99%
“…Hemsworth, Muterera & Baregheh 2013;Kirkbride 2006;Muenjohn & Armstrong 2008;Ozaralli 2003), which confirms that it is an appropriate instrument for adequately capturing the constructs of transformational leadership. Organisational citizenship was measured using six items adapted from the 'Organisational Citizenship Behaviour Checklist' developed by Spector et al (2010) and validated by Gualandri (2012), as well as Uzonwanne (2014). Quality of work life was measured using five items adapted from the WRQoL scale developed by Van Laar et al (2007).…”
Section: Measurement Instrumentmentioning
confidence: 99%